Effects of Pulmonary Rehabilitation on Disease Control, Quality of Life, and Functional Capacity of Individuals with Severe Asthma (CIPEEX, 2025)
Severe asthma is a chronic airway inflammation characterized by remodeling, hyperresponsiveness, and persistent symptoms, resulting in high morbidity. Pulmonary rehabilitation has been shown to improve ventilatory capacity, reduce symptoms, and modulate inflammation, with physical exercise exerting important anti-inflammatory effects. Bradykinin and other kinins play a role in bronchoconstriction and airway inflammation, and understanding this relationship may broaden therapeutic strategies. This study aimed to evaluate the impact of pulmonary rehabilitation on disease control, quality of life, and functional capacity of individuals with severe asthma. Twenty-one patients diagnosed with severe asthma according to GINA criteria, aged between 20 and 60 years, without comorbidities and under continuous medication use for at least six months, were included. Asthma control was assessed using the Asthma Control Questionnaire (ACQ7), quality of life through the Asthma Quality of Life Questionnaire (AQLQ), and functional capacity with the six-minute walk test following American Thoracic Society (ATS) guidelines. Data normality was tested with Kolmogorov-Smirnov, and comparisons were performed using Student’s t-test, with significance set at p
Keywords: Asthma; Quality of Life; Rehabilitation; Functional Capacity